Enhanced circuit for linear ring VCO‐ADCs. Issue 10 (1st May 2019) - Borgmans, J.; Rombouts, P.
Abstract : Recently an extremely linear voltage‐controlled ring‐oscillator for use in VCO‐ADCs was proposed by Babaie‐Fishani and Rombouts. In this current Letter, a circuit‐level technique to improve the bandwidth and noise performance of such a linear VCO is proposed. The key element is the modified delay cell, where the traditional cross‐coupled inverters are modified into 'feed‐forward' coupling inverters that pre‐charge the subsequent elements in the ring. The resulting circuit maintains the excellent linearity, but has greatly enhanced bandwidth (up to 3 times higher) and considerably reduced power for the same circuit noise level (up to 2.5 times lower).